Chlorogenic acid and caffeic acid from Sonchus oleraceus Linn synergistically attenuate insulin resistance and modulate glucose uptake in HepG2 cells. (May 2019) - Chen, Lei; Teng, Hui; Cao, Hui
Abstract: The crude extract of Sonchus oleraceus Linn (CE) and its main phenolic acids (PA), chlorogenic acid and caffeic acid have anti-diabetic activity, but the mechanisms for their effects on glucose intake remain largely unknown. Aim of this study was to examine the synergistic effect of chlorogenic and caffeic acid from S. oleraceus Linn attenuate insulin resistance and modulate glucose uptake in HepG2 cells. Major phenolic acids in SOL were isolated and identified by HPLC. Insulin-resistance HepG2 cell model was used to elucidate the effect of CE on glucose metabolism. Pre-treatment of HepG2 cells with CE or PA enhanced levels of glucose production and avoided the decrease total levels of IRS-1 triggered by high insulin concentration. CE or PA pre-treatment also could prevent the inactivation of the PI3K/AKT pathway, as well as the diminution of GLUT4 levels induced by high glucose. These findings suggested that CE and its main phenolic acids improved insulin sensitivity of HepG2 cells treated with insulin, preventing or delaying a potential hepatic dysfunction through the attenuation of the insulin signaling blockade and the modulation of glucose consumption. Highlights: Sonchus oleraceus Linn (CE) and its phenolic acids (PA) have antidiabetic effects. Phenolic acids synergistically effect on insulin resistance and glucose uptake in HepG2 cells. CE or PA enhanced levels of glucose production in insulin-resistance HepG2.